Calculation of compensation and damages in international investment law - Marboe, Irmgard (Oxford, United Kingdom Oxford University Press, 2017)
"[This] this title analyses the practice of international courts and tribunals with regard to the valuation of investment claims against states, paying specific attention to the question of interest. This new edition incorporates new jurisprudence, updates existing cases, and includes a new section on immaterial damage. The new edition also contains extensive annexes devoted to ICSID cases and non-ICSID investment cases, as well as a table on methods of valuation in international practice. This issue of valuation represents one of the most important aspects of international investment disputes. The parties involved have an obvious interest in an appropriate solution to the question of the quantum of damages. The sums involved are high and this is particularly true in the context of private foreign investment. With the increase in international investment both in the developing as well as the developed world, there is a growing need for a stable and predictable approach to quantum. This new edition meets the needs of foreign investors and host states by setting the issue of valuation on more solid ground. It provides an analysis of how international courts and tribunals have handled cases until now. The emphasis lies on the correct identification of the legal basis claim to inform the valuation method. The author concludes with suggestions and proposals as to how valuation should be handled by legal councils, experts, judges, and arbitrators in international judicial proceedings."--
The function of compensation and damages -- Valuation standards and criteria -- International standards, bases of value, and valuation approaches -- Methods of valuation in international practice -- Interest.
Includes bibliographical references (pages 517-538) and index.
Keywords: Investments, Foreign -- Law and legislation; Damages; Compensation (Law); Compensation (Law); Damages; Investments, Foreign -- Law and legislation